A SKETCH OF THE WORLD AFTER THE COVID-19 CRISIS: ESSAYS ON POLITICAL AUTHORITY, THE FUTURE OF GLOBALIZATION, AND THE RISE OF CHINA - Caron, Jean-François (Palgrave MacMillan, 2020)
This introductory section identifies how the Covid-19 may either contribute to exacerbate the current problems of Political Modernity or accelerate certain political phenomena that may result in challenges to the world order.
Keywords: Covid-19